Pemanfaatan Media Sosial Tiktok Sebagai Sarana Promosi Kripik Jamur Tiram - Sri Hariyanti (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
The development of technology is increasingly rapid and unstoppable, making all aspects of people's lives inseparable from digital activities. Likewise, the world of commerce has begun to shift from offline activities to online activities. Digital marketing aims to promote products and increase sales with various digital marketing techniques. This study uses a qualitative descriptive approach with the aim of knowing the use of Tiktok social media as a means of promoting oyster mushroom chips. The results of this study that CV. Ardhanafood has used a TikTok account with the name @ardhanafood as a means of promoting oyster mushroom chips with 12.9K followers. Compared to other applications, tiktok currently has several advantages, including no need to have tiktok to view videos, that is, everyone can see videos on tiktok without having a tiktok account, has various filters so that they can be as creative as they want, to attract viewers who see, have challenges. , free to use background music that is currently viral or that is being widely used so that it can attract more viewers, as well as to attract new consumers.